Patterns of cervical spine injuries in adults at a major trauma center in Saudi Arabia - Alharbi, Ahoud (Saudi Med J, 2020)
OBJECTIVES: To describe the patterns of cervical spine injuries in an adult population in a major trauma center in Riyadh, Saudi Arabia. METHODS: A retrospective cohort study including all adults with cervical spine injuries from 2014 to 2018 was conducted. All patient data with radiological evidence of injury involving the cervical spine were collected. RESULTS: The final sample size realized as 257 patients. Majority of the sample (85.6%) were male and the age ranged from 14-90 years (mean of 36.6 years±18.5 SD). Motor vehicle accidents were the most frequent mechanism of injury (92.6%, n=238). Single level of injury of the cervical spine was encountered in 52.9% (n=136) and 2 or more levels of injury were encountered in 47.1% (n=122) of patients. In total, 442 cervical spine injury levels were identified. At these levels, 559 fractures were observable radiologically. Associated head injury was present in 125 patients (48.6%). Only a small proportion (22.2%, n=57) had neurological sequelae. CONCLUSION: It reflects the impact of this injury on younger male patient population.